2010
DOI: 10.1007/s10856-010-4128-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(d/l-lactide-co-l-lactide) hybrid matrix: a novel scaffold material for soft tissue engineering

Abstract: Electrospinning is a long-known polymer processing technique that has received more interest and attention in recent years due to its versatility and potential use in the field of biomedical research. The fabrication of three-dimensional (3D) electrospun matrices for drug delivery and tissue engineering is of particular interest. In the present study, we identified optimal conditions to generate novel electrospun polymeric scaffolds composed of poly-d/l-lactide and poly-l-lactide in the ratio 50:50. Scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Because biodegradability is an essential material requirement in tissue engineering, numerous potentially biodegradable polymers including poly(α-hydroxy acids) and their copolymers [11], polyanhydrides [12], collagen [13], gelatin [14], chitosan [15], or silk [16] have been used to fabricate scaffolds for cell culture. Numerous studies have shown that different types of cells including osteoblasts [17], chondrocytes [18], fibroblasts [19], keratinocytes [20], or cardiomyocytes [21] are able to adhere and proliferate well when cultured on those electrospun scaffold materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because biodegradability is an essential material requirement in tissue engineering, numerous potentially biodegradable polymers including poly(α-hydroxy acids) and their copolymers [11], polyanhydrides [12], collagen [13], gelatin [14], chitosan [15], or silk [16] have been used to fabricate scaffolds for cell culture. Numerous studies have shown that different types of cells including osteoblasts [17], chondrocytes [18], fibroblasts [19], keratinocytes [20], or cardiomyocytes [21] are able to adhere and proliferate well when cultured on those electrospun scaffold materials.…”
Section: Introductionmentioning
confidence: 99%
“…One approach could imply electrospun materials [17,18], or hydrogels [19,20] with natural or synthetic materials. Hydrogels are still commonly used as scaffolds in tissue engineering [21].…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning has gained much interest as a processing technique providing promising scaffold structures in soft tissue engineering [17,22]. This technique offers high flexibility in material selection of synthetic and also natural polymers with porous nano or micro structured three-dimensional structure that imitates the extracellular matrix and supports the mechanical stability of tissue [23].…”
Section: Discussionmentioning
confidence: 99%
“…Electrospun nano-fiber substrates have many favorable properties, such as high surface area-to-volume ratio, nano-topographical features, and polymer concentration (James et al 2008; Kumbar et al 2008). Furthermore, electrospinning accompanying nanotechnology process emerges as a versatile and particular technique to form fibers with diameter in the range from µm down to nm to produce fiber substrates that simulate the architecture of native extracellular matrix (ECM) (Irani et al 2013; James et al 2008; Kluger et al 2010). Thus, nano-fibers were fabricated through electrospinning technique due to the advantages to repair and regenerate the tissue in bioengineering (Cheng et al 2014; Guadalupe et al 2015).…”
Section: Introductionmentioning
confidence: 99%